Impact of the Expert Consensus on Carbapenem Consumption Trends and Patterns in Public Healthcare Institutes: An Interrupted Time Series Analysis, 2017–2020 - Ye, Dan; Yang, Caijun; Ji, Wenjing; Zheng, Jie; Zhang, Jingyi; Xue, Runqing; Gu, Jianli; Chen, Minchun; Yan, Kangkang; Liu, Yongzhong (Frontiers in Pharmacology, 2022)
Background: Carbapenems are considered the last line of defence against bacterial infections, but their high consumption and the resulting antibacterial resistance are an increasing global concern. In this context, the Chinese health authority issued an expert consensus on the clinical applications of carbapenems. However, the long- and short-term effects of the expert consensus on carbapenem use are not clear. Methods: This study was conducted in Shaanxi, a northwest province of China. We collected all available carbapenem procurement data between January 2017 and December 2020 from the Provincial Drug Centralized Bidding Procurement System. A quasi-experimental interrupted time series analysiswas used to evaluate the longitudinal effectiveness of expert consensus by measuring the change in the Defined Daily Doses per 1000 inhabitants per day (DID), the percentage of carbapenem expenditures to total antimicrobial expenditure, the total carbapenem expenditure, and the defined daily cost (DDDc). We used Stata SE version 15.0 for data analysis, and p<0.05 was considered statistically significant. Results: After the distribution of the expert consensus, the level (p=0.769) and trend (p=0.184) of DID decreased, but the differences were not statistically significant. The percentage of carbapenem expenditures to total antimicrobial expenditure decreased abruptly (p＜0.001) after the intervention, but the long-term trend was still upward. There was no statistically significant relationship between the release of the expert consensus and carbapenem expenditure in the long term, but there was a decreasing trend (p=0.032). However, the expert consensus had a positive impact on the economic burden of carbapenem usage in patients, as the level (p＜0.001) and trend (p=0.003) of DDDc significantly decreased. Conclusions: The long-term effects of the distribution of the expert consensus on the use and expenditure of carbapenems in public health institutions in Shaanxi Province were not optimal. It is time to set up more administrative measures and scientific supervision to establish a specific index to limit the application of carbapenems.